1994
DOI: 10.1172/jci117459
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen mediates platelet-polymorphonuclear leukocyte cooperation during immune-complex glomerulonephritis in rats.

Abstract: The metabolic and functional alterations which occur during the acute phase of nephrotoxic nephritis (NTN) in rats, a model of immune-mediated glomerulonephritis, result from a cooperative interaction between PMNs and platelets (PLTs). In consequence, we hypothesized that fibrinogen (Fg) might play a critical role in this process and, accordingly, we found that defibrination of animals decreased both the acute phase proteinuria in NTN (-70%) as well as the influx of PLTs and PMNs into the glomerulus (-40-50%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 33 publications
2
39
0
Order By: Relevance
“…In NTN, deposition of fibrin and fibrinogen is observed in glomeruli, and inhibition of thrombosis prevents severe renal damage (25,26). We also confirmed less fibrin deposition in Gas6 -/-mice than in wild-type mice by electron microscopy (data not shown).…”
supporting
confidence: 64%
“…In NTN, deposition of fibrin and fibrinogen is observed in glomeruli, and inhibition of thrombosis prevents severe renal damage (25,26). We also confirmed less fibrin deposition in Gas6 -/-mice than in wild-type mice by electron microscopy (data not shown).…”
supporting
confidence: 64%
“…a M b 2 (Mac-1, CD11bCD18) is a principal neutrophil integrins, which, upon inflammatory challenges, undergoes conformational change for high affinity/avidity binding to its ligands, such as fibrinogen (Fg) and intercellular cell adhesion molecule-1 (ICAM-1, CD54). [8][9][10][11][12][13] The close proximity and the timing rendered by selectin-mediated leukocyte rolling are generally believed to facilitate b 2 -integrin activation by extracellular stimuli, such as interleukin-8 (IL-8), platelet activating factor (PAF), stromal cell-derived factor 1 (SDF-1, CXCL12) and several others. [14][15] They are released from and displayed on the activated endothelial lining of the vessel walls, which dynamically forms the "adhesive zone" with the contact site of rolling leukocytes in situ and locally activates leukocyte integrins in subseconds through pertussis toxin (PTX)-sensitive Gi-type heterotrimeric G-protein coupled receptors (GPCRs).…”
Section: Abbreviationsmentioning
confidence: 99%
“…From the earlier histopathological detection of fibrin in delayed-type hypersensitivity (1) and on tissue macrophages (2), recent experiments have demonstrated that systemic defibrinogenation drastically attenuates inflammatory responses to purulent bacterial infections (3), implanted biomaterials (4), and Ig-mediated acute nephrotoxic nephrites (5) in vivo.…”
Section: Introductionmentioning
confidence: 99%